Plyometric training. Theory and practice - Goodwin, J. E.; Jeffreys, I. (Strength and conditioning for sports performance, 2016)
Plyometric exercises are a group of high-intensity, shock-based methods aimed at enhancing high rates of force production, eccentric control and power. Plyometrics involve receiving loads at high rates (often through high-impact landings) and then generally returning loads at similarly high rates (normally via jumps or throws). These types of activities create unique demands on the musculoskeletal system, both in preparation for receiving loads and during the period of force application, where acute increases in capabilities are seen as a result of the characteristic function of the stretch-shorten cycle (SSC). The enhanced function demonstrated during activities utilising an SSC is reflected in the term `plyometrics`, deriving from the Greek terms plyo-(pleion, meaning increasing) and-metric (metron, meaning measurement or length). Chronic responses to this type of training lead to improvements in the ability to use the SSC. For this reason, plyometric training has become a common form of training in many sports, and has been demonstrated to offer benefits to a wide range of general qualities and specific athletic endeavours including jumping, sprinting, agility and endurance performance (15). The central importance of the SSC in plyometrics, and its relevance to many sporting tasks make the mechanism of function, and therefore potentially adaptation, a topic of interest to the strength and conditioning (S&C) coach.